Hak Waris Pemohon Euthanasia Pasif menurut Hukum Islam: Studi tentang Maqāṣid al-Syarī‘ah (Birthright of Passive Euthanasia Applicants according to Islamic Law: Study of Maqāṣid al-Syarī'ah) - M. Yunus, Fakhrurrazi; luthfiani, amira (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2019)
Such rapid development of science and technology lately resulted in such rapid changes in the social life of the human culture, one of which is medical field. But although there has been no progress there may be some problems that have not been solved by human beings, such as the discovery of drugs or a potent bidder to cure deadly diseases such AS AIDS, cancer, and other malignant diseases. These deadly diseases are a reason for someone to end his life from having to endure a long time ill one of them by asking for family assistance to end his life, which in medicine is called euthanasia. This research aims to determine how the position of passive euthanasia and birthright position for applicants of euthanasia passive according to Islamic law when viewed in terms of maqāṣid al-Syarī'ah. This research is done by collecting the library materials in the form of books, encyclopedia, and scientific works related to this discussion. The results of this study gave the answer that stopping the treatment, or releasing the organ and respiratory aids from the sick or euthanasia passive the law may but only in the case of the sick suffer the death of the brainstem. Because while using these tools is contrary to sharia teachings among them, postponing the management of dead and its funeral without emergency reasons, postponing the division of inheritance and resigning the time of his wife. Therefore, the birthright position for the heir or the family that asks or plea for passive euthanasia is not hindered by the heir. Because the passive euthanasia in this case is not classified as an act of murder.